Laser additive manufacturing of powdered bismuth telluride. Issue 23 (6th November 2018) - Zhang, Haidong; Hobbis, Dean; Nolas, George S.; LeBlanc, Saniya
Abstract: Abstract : Traditional manufacturing methods restrict the expansion of thermoelectric technology. Here, we demonstrate a new manufacturing approach for thermoelectric materials. Selective laser melting, an additive manufacturing technique, is performed on loose thermoelectric powders for the first time. Layer-by-layer construction is realized with bismuth telluride, Bi2 Te3, and an 88% relative density was achieved. Scanning electron microscopy results suggest good fusion between each layer although multiple pores exist within the melted region. X-ray diffraction results confirm that the Bi2 Te3 crystal structure is preserved after laser melting. Temperature-dependent absolute Seebeck coefficient, electrical conductivity, specific heat, thermal diffusivity, thermal conductivity, and dimensionless thermoelectric figure of merit ZT are characterized up to 500 °C, and the bulk thermoelectric material produced by this technique has comparable thermoelectric and electrical properties to those fabricated from traditional methods. The method shown here may be applicable to other thermoelectric materials and offers a novel manufacturing approach for thermoelectric devices.